2021
DOI: 10.1177/13694332211026222
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the effect of weathering and corrosion on the bond properties of bamboo- and steel-reinforced cement-stabilized rammed earth blocks

Abstract: In this article, the effect of weathering and corrosion on the bond properties of bamboo- and steel-reinforced cement-stabilized rammed earth blocks was investigated. The treated, untreated bamboo and steel reinforcement types were considered under regular and weathered categories. Reinforcement of 8 mm, 10 mm and 12 mm diameters were used along with 10% of cement as stabilizer. A total of 90 reinforced cement-stabilized rammed earth blocks were prepared and tested for bond strength. The investigation shows th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Figures 4(a rough comparison, we found that at this time, because the chloride ion in the artificial seawater has a shallow erosion depth, it has not contacted the reinforcement in the test piece at all, and the different erosion environment has not affected the development of the passive film on the surface of carbon steel for the time being. ere are only chloride ions contained in the aggregate surface and mixing seawater around the reinforcement, so the Nyquist diagrams of L1 and L2 in the first week are completely consistent [17,18]. In further experiments, the arc resistance of L1 and L2 capacitances in the frequency range was the difference of 84 days, indicating that during this time, the effects of differential corrosion of carbon steel begins to appear slowly.…”
Section: Electrochemical Impedancementioning
confidence: 76%
“…Figures 4(a rough comparison, we found that at this time, because the chloride ion in the artificial seawater has a shallow erosion depth, it has not contacted the reinforcement in the test piece at all, and the different erosion environment has not affected the development of the passive film on the surface of carbon steel for the time being. ere are only chloride ions contained in the aggregate surface and mixing seawater around the reinforcement, so the Nyquist diagrams of L1 and L2 in the first week are completely consistent [17,18]. In further experiments, the arc resistance of L1 and L2 capacitances in the frequency range was the difference of 84 days, indicating that during this time, the effects of differential corrosion of carbon steel begins to appear slowly.…”
Section: Electrochemical Impedancementioning
confidence: 76%
“…Rathod, B., et al [ 35 ] focused on cement stabilized earth-based matrix with dry density, cement content, and moisture content and coir fibers with different embedment lengths by pull-out test. In addition, some research reported that bond behavior of other pull-out objects such as rebar [ 36 ], steel [ 37 ], bamboo [ 38 ] and timber [ 39 ] in cement stabilized earth-based matrix mainly with diverse factors including dry densities and content of the matrix as well as geometric properties and types of pull-out objects. Hence, current studies have not sufficient explored the earth-based matrix.…”
Section: Introductionmentioning
confidence: 99%